Mechanical response of deep circular shaft supported by steel frame and sprayed concrete in loess-paleosol sequence: A case study - Jiawei Kang; Guohua Deng; Shengjun Shao; Liqin Wang (Case Studies in Construction Materials)
Loess has a large pore structure and well-developed vertical joints, belonging to a strong structural soil layer with good self-supporting properties. Generally, the actual lateral pressure exerted on underground structures is relatively small and its distribution is complex. A deep circular shaft, 53.5 m deep and 9.6 m in diameter, was constructed in the loess-paleosol sequence in China, supported by a steel frame and sprayed concrete. This study analyzes special mechanical responses of a deep shaft in loess-paleosol sequences, focusing on shaft lining deformation patterns, ground settlement influence zones, and lateral pressure distribution characteristics. The main conclusions are as follows: (1) Various physical property indexes, horizontal deformation, and lateral pressure of the shaft lining exhibit fluctuations within the loess-paleosol sequence. (2) The measured maximum horizontal deformation of the shaft lining is less than 10 mm. The shallow and deep shaft linings show distinct convergence patterns. (3) After excavation, the deep lining's horizontal convergence, lateral pressure, and internal force in the secondary lining continues to develop for 25–172 days and gradually stabilizes. (4) The ground settlement influence zone is 1.5 R, while the horizontal deformation zone is less than 0.35 R, the lateral pressure on the shaft lining peaks at 0.45 H, the maximum d/H is 0.03 %. (5) The lateral pressure on shaft lining in the loess layer approaches the Rankine active soil pressure under minimal deformation, while that in the paleosol layer is only 30 % - 50 % of its active soil pressure.